2014
DOI: 10.15253/2175-6783.2014000300014
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal outcome in pregnancies that presented premature rupture of membranes

Abstract: This study aimed to describe the neonatal outcomes of infants whose mothers had premature rupture of membranes during pregnancy. This is a retrospective, descriptive, quantitative study performed in a public maternity in Fortaleza-CE, Brazil, with 166 neonates of mothers with premature rupture of membranes, in 2010. Data were collected through research in medical records using a pre-structured form. There was a predominance of newborns at term with good birth weight and adequate vitality. Statistical analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
2
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 14 publications
0
8
2
1
Order By: Relevance
“…These American authors also established a rate of 11.8% for previous PPROM; this rate was higher than the rate of 1.6% reported for the control population, thus yielding an OR=8.3. However, our rates are still higher than those indicated by a survey carried out in the Brazilian northeast (11), where 5.4% of pregnant women with PPROM had a history of PPROM, and 4.8% had previous prematurity. A classic study on the subject (39) previously indicated that previous premature birth was an important risk factor for PPROM, with OR=2.5.…”
Section: Discussioncontrasting
confidence: 83%
See 4 more Smart Citations
“…These American authors also established a rate of 11.8% for previous PPROM; this rate was higher than the rate of 1.6% reported for the control population, thus yielding an OR=8.3. However, our rates are still higher than those indicated by a survey carried out in the Brazilian northeast (11), where 5.4% of pregnant women with PPROM had a history of PPROM, and 4.8% had previous prematurity. A classic study on the subject (39) previously indicated that previous premature birth was an important risk factor for PPROM, with OR=2.5.…”
Section: Discussioncontrasting
confidence: 83%
“…Considering occupation, almost half of the patients analyzed (44.1%) described themselves as housewives (or as domestic workers). This rate may appear high, but it is lower than the rates reported by other authors in Fortaleza-Ceará, in the Brazilian northeast (11), of 49.7%, or in Cuba (25), of 71.4%. The latter study found among the housewives a 1.5-fold higher relative risk of PROM after the 30 th week of pregnancy.…”
Section: Discussioncontrasting
confidence: 61%
See 3 more Smart Citations